С.МӘЖИЙТОВ ШЫҒАРМАЛАРЫНДА ФРАЗЕОЛОГИЗМЛЕРДИҢ ҚОЛЛАНЫЛЫЎ ӨЗГЕШЕЛИКЛЕРИ - Диланов, Б.Г. (FAN va JAMIYAT, 2023)
This article is about phraseological units, which are reflected in the works and teaching guides of S. Madzhitov, a prominent educator, poet and playwright of the early 20th century. In the works of the poet, to strenghthen the meaning of phraseological units, different words are included in its compound, various variants of stable combinations appeared.